Dampak Penetapan Pajak Rokok Terhadap Peneriman Pajak Daerah di Daerah Istimewa Yogyakarta - Ihda Arifin Faiz; Zumala Anis Surayya (Jurnal Gama Societa, 2017)
Consider Law No. 28 from 2009 on Local Taxes and Retribution, Local Governments may collect any taxes on cigarettes that should broadening locally-generated revenue. Thus, application of the cigarette tax revenue should increase local income significantly. This study examines the impact of the cigarette tax collection on local tax revenue in the Special Region of Yogyakarta. The research data is sourced from the Local Government Budget Realization Report in Special Region of Yogyakarta. The data used in this study was examined used Paired Sample T-test, comparing the Local Tax Income before 2013 and after 2014, where years of the Cigarette Tax enactment.  The results of this study show that there was no significant difference in Local Tax Income before and after the enactment of the Cigarettes Tax in Yogykarta. Results of this study can be used to produce recommendations for the central government in determining potential and realization of the cigarette tax to the local government.